1995
DOI: 10.1084/jem.182.6.1751
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a CD4+ T cell-stimulating antigen of pathogenic bacteria by expression cloning.

Abstract: SummaryIdentifying the immunogenic proteins that elicit pathogen-specific T cell responses is key to rational vaccine design . While several approaches have succeeded in identifying major histocompatibility complex (MHC) class I bound peptides that stimulate CD8+ T cells, these approaches have been difficult to extend to peptides presented by MHC class II molecules that stimulate CD4 + T cells. We describe here a novel strategy for identifying CD4 + T cell-stimulating antigen genes. Using Listeria monocytogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…[24][25][26] In addition to utilising this system as a vaccination strategy for tumour immunotherapy, infecting DCs with recombinant E. coli/LLO may represent an efficient method for identifying new tumour antigens from either potential cDNA candidates specifically expressed on tumours that could be identified by microarray analysis, or by screening tumour cDNA libraries against tumourspecific CTL. A similar approach has already been utilised to identify novel human CD4 + -restricted antigens from Mycobacterium tuberculosis, 27,28 and the addition of LLO would allow the identification of antigens recognised by CTLs.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] In addition to utilising this system as a vaccination strategy for tumour immunotherapy, infecting DCs with recombinant E. coli/LLO may represent an efficient method for identifying new tumour antigens from either potential cDNA candidates specifically expressed on tumours that could be identified by microarray analysis, or by screening tumour cDNA libraries against tumourspecific CTL. A similar approach has already been utilised to identify novel human CD4 + -restricted antigens from Mycobacterium tuberculosis, 27,28 and the addition of LLO would allow the identification of antigens recognised by CTLs.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the cognate antigen recognized by BTg01Z.A hybridoma by expression cloning. We have previously shown that recombinant Escherichia coli expressing a variety of proteins can serve as an exogenous antigen source for MHC class II presentation pathway in bone marrow-derived macrophages or DCs (BMDCs) and that detection of these antigens with the appropriate T cell hybridoma can be used to identify the relevant antigen (8,50,51). We used this approach to screen a T. gondii cDNA library (see Materials and Methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…The use of a proven protective T cell line as the readout of the T cell expression cloning approach is an attractive alternative. This approach, initially developed for the identification of a leishmanial and a listerial gene encoding T cell Ags (45,46), was recently described as a powerful strategy for the direct screening and cloning of genes from a M. tuberculosis genomic expression library (36) using human M. tuberculosis reactive T cell lines as readouts. Here, the use of this technology, employing a proven protective murine CD4 ϩ T cell line, resulted in the cloning of several potentially protective genes.…”
Section: Discussionmentioning
confidence: 99%